Impact of an Educational Program upon Academic Nurses’ Practice Concerning Documentation of Nursing Sheets in the Medical and Surgical Teaching Hospitals of Sulaimani Governorate - Samir Y. Lafi, (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: The study objectives are to determine the impact of education program upon the academic nurses'practice concerning documentation of nursing sheets, and to find out the relationship between nurses knowledgeand their demographic characteristics, which include age, sex, and years of experience in medical and surgicalwards.Methodology: A quasi- experimental study was carried out at the medical and surgical wards in teachinghospitals in Sulaimani governorate from the beginning of March up to June 2007٠To reach the objectives of the study anon-probability (purposive) sample of (25) academic nurses who work inthe medical and surgical wards in teaching hospitals.The data were collected through the use of constructed questionnaire, which comprised of demographicinformation and scientific knowledge concerning nursing documentation which include (19) items.The reliability of the instrument was determined through test-retest, ([20.86) and the validity through a panel of14 experts.The data were analyzed through the application of descriptive statistical analysis and the application ofinferential statistical analysis.Results: The results of the study indicated that the educational program had appositive impact on theknowledge of the academic nursestowards documentation of nursing sheets.Recommendations: Based on the results of the study, the investigator recommended that academic nurseswho are working in the teaching hospitals should be encouraged to participate in educational programs andpresent it to the nurses who have minimum level of knowledge in order to improve their level of knowledge,which improve quality of care in the hospitals.Furthermore, the study recommended that a specific educational programs should be designed to other nurses inother nursing specialties.